A study on the monitoring of LNAPL migration using ERT. - Kui Suo; Mingdong Zhao; Yu Liu; Hongwei Liu; Menghan Jia (PLoS ONE)
This study employs electrical resistivity tomography (ERT) to experimentally investigate the migration characteristics of light non-aqueous phase liquids (LNAPL) under various groundwater conditions. Through cross-hole measurements and time-lapse inversion, the migration process of LNAPL under three scenarios-unsaturated conditions, constant groundwater levels, and declining water levels-was systematically analyzed. The results indicate that LNAPL migration behavior exhibits significant differences under different conditions. Under unsaturated conditions, the vertical migration rate of LNAPL gradually decreases over time, with an average rate of 1.06 cm/h, and is influenced by preferential migration pathways formed in coarse-grained regions. At constant water levels, the migration of LNAPL is significantly constrained by the groundwater level, spreading horizontally near the water table after reaching it, with an average rate of 0.51 cm/h. When the groundwater level declines, LNAPL migrates rapidly downward along preferential flow paths, with an average rate increasing to 1.45 cm/h. Miller Soil Box experiments further reveal the relationship between LNAPL content and electrical resistivity, showing that an increase in LNAPL can significantly alter soil resistivity, especially under low moisture conditions. Overall, this study confirms the monitoring advantages of ERT technology for LNAPL migration behavior under different conditions and provides important references for remediation strategies at contaminated sites.